Prediksi Hasil Produksi Kopi Provinsi di Pulau Kalimantan Menggunakan Analisis Rantai Markov - Reynaldy Hutabarat; Satria Rizky Silaban; Septi Melani Putri Tambunan (International Forum of Researchers and Lecturers, 2024)
This research discusses the prediction of coffee production outcomes in Kalimantan using Markov chain analysis. A Markov chain is an analytical technique that can be used to predict future changes based on past changes. The aim of this study is to determine the predicted coffee production results in Kalimantan from 2023 to 2025 based on Markov chain analysis. Based on the results of the Markov chain analysis of coffee production data in Kalimantan from 2018 to 2022, it is concluded that the predicted coffee production results in 2024 are as follows: West Kalimantan Province is expected to produce 3.5632 thousand tons, Central Kalimantan Province 0.3275 thousand tons, South Kalimantan Province 1.3727 thousand tons, East Kalimantan Province 0.1934 thousand tons, and North Kalimantan Province 0.1539 thousand tons. Furthermore, in 2025, the coffee production in West Kalimantan Province is predicted to reach 3.5935 thousand tons, Central Kalimantan Province 0.3304 thousand tons, South Kalimantan Province 1.3857 thousand tons, East Kalimantan Province 0.1952 thousand tons, and North Kalimantan Province 0.1554 thousand tons.